2014
DOI: 10.1891/1945-8959.13.3.292
|View full text |Cite
|
Sign up to set email alerts
|

Leaning Toward a Consensus About Dynamic Assessment: Can We? Do We Want To?

Abstract: This article offers a response to two questions: Can we reach a consensus in the domain of dynamic assessment? and Do we want to? The brief response to these questions is first: Yes, it may be possible to reach a sufficient degree of consensus that we can offer some guidelines as to what is and what is not “dynamic” about assessment. The response to the latter question of whether we want to or not is a more qualified, “Well sort of, and to some extent, but with a great deal of latitude, flexibility, and room f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Dynamic testing can be utilized not only to measure progression in task solving, in terms of accuracy scores on the task considered, but also to assess the processes involved in learning how to solve these problems (Elliott, Resing, & Beckmann, 2018;Haywood & Lidz, 2007;Resing & Elliott, 2011;Sternberg & Grigorenko, 2002). Over the years, several different formats have been developed for dynamic testing (Haywood & Lidz, 2007;Lidz, 2014;Sternberg & Grigorenko, 2002). Formats range from relatively unstructured, with a great emphasis on the examiners' possibility to provide unique individualized instruction at any point the examiner deems necessary, to completely standardized (e.g., Campione, Brown, Ferrara, Jones, & Steinberg, 1985;Resing, 1998).…”
Section: Dynamic Testing and Graduated Prompts Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic testing can be utilized not only to measure progression in task solving, in terms of accuracy scores on the task considered, but also to assess the processes involved in learning how to solve these problems (Elliott, Resing, & Beckmann, 2018;Haywood & Lidz, 2007;Resing & Elliott, 2011;Sternberg & Grigorenko, 2002). Over the years, several different formats have been developed for dynamic testing (Haywood & Lidz, 2007;Lidz, 2014;Sternberg & Grigorenko, 2002). Formats range from relatively unstructured, with a great emphasis on the examiners' possibility to provide unique individualized instruction at any point the examiner deems necessary, to completely standardized (e.g., Campione, Brown, Ferrara, Jones, & Steinberg, 1985;Resing, 1998).…”
Section: Dynamic Testing and Graduated Prompts Proceduresmentioning
confidence: 99%
“…acquired knowledge and skills have to be assessed, but also their potential to learn when the opportunity is presented (Grigorenko & Sternberg, 1998;Sternberg & Grigorenko, 2002). These criticisms led to the development of dynamic testing, which involves testing procedures in which a training session is incorporated to assess the child's response to a learning opportunity (e.g., Kozulin, 2011;Lidz, 2014;Resing, 2013;Sternberg & Grigorenko, 2002;Stringer, 2018). To improve the predictive validity of traditional tests, some researchers argued that an additional analysis of the task solving process would provide valuable information regarding cognitive potential (Resing & Elliott, 2011;Resing, Xenidou-Dervou, Steijn, & Elliott, 2012;Sternberg, & Grigorenko, 2002).…”
mentioning
confidence: 99%
“…Although DA was historically concerned with “pure cognitive functions” and was primarily used as an alternative to traditional intelligence tests (Kozulin, , p. 85), L2 researchers became interested in its use for more specific educational needs (Lantolf & Poehner, ; Poehner, ). The former, Cognitive DA , sought to directly promote the maturation of higher mental functions through cognitive enrichment programs, while the latter, Curricular DA , seeks to modify cognition through concept development within a given subject content (Kozulin, ; Lidz, ). In curricular DA, the goal is concept‐based regulation through which learners internalize complex semantic and pragmatic notions needed to reach higher levels of proficiency (Negueruela–Azarola, García, & Buescher, ).…”
Section: Assessment Learning and Development In Sociocultural Theorymentioning
confidence: 99%
“…Furthermore, the likelihood of test-retest-reliability is highly questionable [98,104]. More recent descriptions of this approach, showing how both standardization of procedures and research designs have improved since the seminal 1979 work, can be found in [96,99,105,106].…”
Section: Dynamic Approaches To Cognitive Testingmentioning
confidence: 99%